Indigenous Development and the Cultural Captivity of Entrepreneurship - Peredo, Ana María; McLean, Murdith (Business & Society, 2013)
This article argues that thinking about entrepreneurship as a potential instrument for relief from endemic poverty and disadvantage, especially among the Indigenous, has all too often been captive to a concept of entrepreneurship that is built out of constrained economic and cultural assumptions. The authors develop this argument from a critical discussion of contributions by Karl Polanyi and Robert Heilbroner. The result is that approaches to venture have been encouraged that are sometimes a poor fit for the circumstances of those they are meant to benefit, and other forms that could have considerable promise have gone unexplored. This article outlines some features of Indigenous culture and build on the analysis of David Harper to construct an improved notion of entrepreneurship that allows for these distinctive features. The article concludes that research and policy making concerning entrepreneurship as an instrument of development among the Indigenous need to be undertaken with this reconstructed understanding of entrepreneurship that is a better fit for the realities of Indigenous culture.
Keywords: HEILBRONER, Robert; Indigenous development; Indigenous peoples; POLANYI, Karl, 1886-1964; cultural diversity; entrepreneurship; entrepreneurship and culture; poverty

Housing Projects for Low-Income Groups and Modes of Economic Integration: A Comparative Study in Greater Cairo - Abouelmagd, Doaa; Kesteloot, Christian; Corijn, Eric (Tijdschrift voor Economische en Sociale Geografie (Journal of Economic & Social Geography), 2013)
The housing of low-income groups in Greater Cairo has always been difficult. However, the general shortage in housing supply is contrasting with the low occupancy rate of newly constructed public housing units. In contrast, despite their bad living conditions, informal settlements have a high occupancy rate. In order to analyse the reasons behind this contradiction, the paper compares four neighbourhoods ranging from formal and semi-informal to informal housing production and including one rehabilitation project. The livelihood conditions in each settlement are unravelled with the concept of modes of economic integration from Polanyi. For this purpose, semi-structured interviews were conducted and analysed with correspondence analysis. The findings indicate a preference among low-income groups for informal settlements because of three reasons: the advantages of geographical location, the nature of social networks and the strength of private redistribution systems, thus enabling an easier access to means of existence. The results and recommendations are further discussed in the paper.
Keywords: Egypt; Greater Cairo; housing rehabilitation; informal settlements; livelihood; living conditions; low-income housing; modes of economic integration; occupancy rates; poor people; public housing; redistribution; squatter settlements

Is Environmental Management Really More Collaborative? A Comparative Analysis of Putative ‘Paradigm Shifts’ in Europe, Australia, and the United States - Benson, David; Jordan, Andrew; Smith, Laurence (Environment and Planning A, 2013)
It is a truism that environmental management has experienced a significant change in the locus of governing, in which centralised forms of steering have been gradually replaced by more collaborative management approaches organised at the ecosystem scale. Whereas much research capital has been expended on informing their design and promoting their uptake, surprisingly little systematic comparative empirical research exists on the precise nature and extent of what is often described as a ‘paradigm shift’ in governing. We address this gap by examining how one issue often deemed to require deeper ‘collaboration’, namely, catchment management, has been addressed in three comparable federal political systems: the European Union; the USA; and Australia. On the basis of a fresh and more comparable account of the forms and modalities of collaboration, we reveal that, although collaboration has undoubtedly grown in recent decades, its depth and extent remains highly variable both across and within the three cases. We also examine what these subtly different geographical ‘contours of collaboration’ imply for future research and practice.
Keywords: catchment management; central control; collaboration; environmental science; federalism; governance; neoliberalism; paradigm shift

Rudderless in a Sea of Yellow: The European Political Economy Impasse for Renewable Transport Energy - Harvey, Mark; Pilgrim, Sarah (New Political Economy, 2013)
Faced with the twin challenges of anthropogenic climate change and ‘peak oil’, the need for an urgent and radical transformation of transport energy has been widely recognised. Adopting a neo-Polanyian economic sociology approach, this article asks what conditions European governance capacity to respond to these challenges, at either national or regional levels, using biofuels as a case study. It asks if the complexity of its political institutions, and the heterogeneity of interests and economic organisations, present ‘the biggest obstacle of all’ (Cohen 2007) to reduce fossil fuel dependency. By examining the European Commission level and comparing five countries, evidence is produced for a political failure in terms of continued fossil fuel dependency. Incumbent interests in the agricultural sector and a distinctively European legacy of a transport fleet dependent on fossil diesel, have led to a marriage of convenience between rapeseed farmers and vehicle manufacturers. As a consequence, rather than escaping from the path dependency on fossil fuels (Unruh 2000), Europe has gone down a cul-de-sac of rapeseed biodiesel inherently limited in scope, and with the low levels of greenhouse gas emissions savings. Ironically this outcome is in part an unintended consequence of opposition to biofuels from environmentalist groups and politics.
Keywords: agriculture; biodiesel fuels; biofuels; biomass energy research; climate change; climate change research; economics; peak oil; politically instituted markets; rapeseed